A Review on Weather Forecast Using Various Soft Computing Techniques - Praveena , Dr. Y. Kalpana (International Journal of Advanced Science and Technology, 2020)
Weather conditions and atmosphere Extremes provide monitoring and early warning to academic, internal improvement agencies, government, nongovernment organizations with publication in different aspect of study in weather and climate changes, More weather forecast similar to precipitation prophecy, shower prophecy, predict obscure circumstances, predict drought and flood, which is vital for farming behavior and water resources organization are main challenges for atmospheric study. Weather and climate analysis has been living its critical role in meteorology and become one of the majority challenge troubles equally scientifically and technologically all larger than the world for the last century. In this article we are learning the different weather and environment model and climate and temperature types, over view of weather and climate. This study also analyses the Data mining techniques and algorithms for the weather condition and environmental changes.